Comparison of ultrasound, mammography and histopathology findings of the cases with gynecomastia - Beyazal Çeliker, Fatma; İnci, Ercan and Sever, Nurten and Cimilli, Ahmet Tan and Turan, Arzu (International Journal of Research in Medical Sciences, 2017)
Background: Gynecomastia is the development of a fibroepithelial structure in the male breast as a result of many benign and malignant effects. In this study, after the confirmation of gynecomastia diagnosis in the male cases with swelling, mass and tenderness in the breast using ultrasound and mammography examinations, its etiology was clarified by laboratory tests. In case of suspicion, the diagnosis was confirmed using Fine-Needle Aspiration Biopsy (FNAB). The adequacy of ultrasound and mammography was discussed with the obtained information and the information in the literature, and the etiological and radiological classification was done. Methods: Ultrasound and mammography examinations were performed on 74 male patients with growth, palpable masses or pain in the breast. Biochemistry and hormone analysis were performed with imaging methods in the cases of possible gynecomastia. Biopsy was performed on the cases with the suspicion. Results: Gynecomastia were divided into three types in ultrasonic and mammographic examination. The most frequent gynecomastia was observed as Type 3 (51.43%) in ultrasonic examination and as diffuse type (61.42%) in mammographic examination. Pain and tenderness accompanied with swelling at the breast were present in 37.84% of the cases. 31.42% had pubertal gynecomastia, 25.71% had gynecomastia secondary to drug use, and 15% had idiopathic gynecomastia. Conclusions: Combined use of ultrasound and mammography in the diagnosis and classification of gynecomastia is highly sufficient and biopsy should be performed if malignancy is suspected.